Visual culture and politics in the Baltic sea region, 1100-1250 - Markus, Kersti, 1962- (East Central and Eastern Europe in the Middle Ages, 450-1450, 2020)
Focusing on visual sources and the cultural landscape, Kersti Markus offers a fresh perspective on the Baltic crusades in Visual Culture and Politics in the Baltic Sea Region, 1100-1250 . The book examines how visual propaganda was used by the Danish rulers as an instrument in establishing supremacy in the Baltic Sea region. In recent decades, Danish historians have highlighted the central role of the Valdemar dynasty and the bishops supporting them in the Baltic crusades, but visual sources show how the entire society was mentally prepared for a journey with redemption waiting at the end. A New Jerusalem was being built in Scandinavia, and the crusade to Livonia was conducted under the banner of Christ.